IN MANAGING THE EDUCATIONAL PROCESS MANAGEMENT RESPONSIBILITY - Dilshoda Raximova; Khoshim Khidirov (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
The article discusses the specifics of leadership responsibilities in the management of the education system, the responsibility of the manager to work with teachers in different situations, knowledge, skills and abilities of the teacher, experience, professionalism, resourcefulness, entrepreneurship and creativity.